2016
DOI: 10.5130/ajceb.v16i3.4993
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model of psychological contracts in construction projects

Abstract: The strategic importance of relationship style contracting is recognised in the construction industry. Both public and private sector clients are stipulating more integrated and collaborative forms of procurement. Despite relationship and integrated contractual arrangement being available for some time, it is clear that construction firms have been slow to adopt them. Hence it is timely to examine how social exchanges, via unwritten agreement and behaviours, are being nurtured in construction projects. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…For construction projects, the previous researches are shown in Table 1. Some scholars have studied the PC of both sides of project procurement and found that PC had a significant impact on fairness, trust, satisfaction, and project performance [5][6][7]. As a special form of procurement, the PC between important stakeholders (public sector and supplier) will affect sustainable project management and sustainability of project development.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…For construction projects, the previous researches are shown in Table 1. Some scholars have studied the PC of both sides of project procurement and found that PC had a significant impact on fairness, trust, satisfaction, and project performance [5][6][7]. As a special form of procurement, the PC between important stakeholders (public sector and supplier) will affect sustainable project management and sustainability of project development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a special form of procurement, the PC between important stakeholders (public sector and supplier) will affect sustainable project management and sustainability of project development. However, unwritten psychological contracts are often ignored by stakeholders [5,6].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations